“Yes, Master”: An Analysis of Language Control in Iron Man through Jarvis, Friday, and Veronica from the Lens of Orwellian Linguistics - Krisdini Ambarsari; Nayla Adzra Suhada (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2025)
In the Marvel Cinematic Universe (MCU), one of the superheroes most closely associated with technology is Iron Man. He built and operated advanced digital life assistants that embody technological sophistication. He controls these AI systems primarily through voice recognition, where language serves as the medium of command and control. Through verbal instructions, he exercised linguistic authority to operate his AI assistants, most notably Jarvis, Friday, and Veronica. This research explores the principle of language control in human-to-AI interaction, as portrayed in the MCU. It specifically investigates the categories of language control, such as deletions, substitutions, and reordering, based on Orwellian Linguistics as formulated by Hodge and Fowler (1979). Drawing parallels between Orwellian Linguistics and human-to-AI interaction, this research adopted a descriptive qualitative design, employing Spradley’s (2016) analytical framework. The findings revealed that deletions, substitutions, and reordering were applied by the speaker (Iron Man) as mechanism of control over the AI assistants. This suggests that the dynamics of language and control are not limited to human-to-AI interactions but may also extend to human-to-human communication in a persuasive or authoritative contexts. Further research could expand this investigation through comparative analyses of human-AI interaction across various film productions.